THE EFFECT OF IMPLEMENTATION OF ONE STUDENT ONE CLIENT (OSOC) ASSISTANCE MATERNITY SERVICE MODEL TOWARD ANXIETY AMONG PRIMIPAROUS MOTHER IN THE POST PARTUM PERIOD - Muliatul Jannah; ROSYIDAH HANIFATUR (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Background: Labor is an event and experience in a woman's life. After giving birth, a mother experiences a postpartum period or puerperal period that is a recovery period. Uncomfortable feeling can cause anxiety, especially in primiparous mothers. Therefore, not to have an impact rise in stress, even untill postpartum depression, a midwife as a spearhead of provider maternal health care must be able to reduce the anxiety which experiences of postpartum mothers, especially primiparous through assistance ‘OSOC’ methods. Objective: To determine the effect of the application of the OSOC assistance maternity service model toward anxiety among primiparous mothers in the postpartum period at Kendal District Health Center. Research Methods: Quantitative data analysis was used to assess the anxiety of postpartum primiparous mothers with the intervention group and the control group, a type of Quasi Experiment research with a non-equivalent control group design. The subjects of this research was divided into two groups, they were intervention groups and control groups. In the intervention group, it was given in the form of providing OSOC assistance in the postpartum period, while the control group was given conventional puerperal care. The research at Kendal District Health Center in May-October 2019. Results: There was a significant difference between anxiety in primiparous postpartum mothers with OSOC conventional assistance, and the magnitude of the effect of mentoring pregnant women with OSOC on anxiety by 7.804. Conclusions: There was a significant difference between anxiety in primiparous postpartum mothers with OSOC and conventional assistance.